International Journal of Earth Sciences GR Geologische Rundschau - Dullo, Wolf-Christian.; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
The International Journal of Earth Sciences publishes process-oriented original and review papers on the history of the earth, including - Dynamics of the lithosphere - Tectonics and volcanology - Sedimentology - Evolution of life - Marine and continental ecosystems - Global dynamics of physicochemical cycles - Mineral deposits and hydrocarbons - Surface processes.
Keywords: Geochemistry; Geology; Structural geology; Sedimentology; Geophysics; Geology; Geophysics/Geodesy.; Sedimentology; Structural Geology; Mineral Resources; Geochemistry